Prinsip Etik Keperawatan Respect to Others Berpengaruh Positif dengan Kinerja Perawat (Journal of Telenursing (JOTING), 2024)
This research aims to identify the relationship between the application of nursing ethical principles and nurse performance. The method used was quantitative with a cross-sectional approach to 129 nurses on duty in the Inpatient Room at RSAL Dr. Mintohardjo. Data analysis was carried out using a linear regression test. The research results show that factors related to performance include rank or class (p=0.037), respect for others (r=0.621), compassion (r=0.594), advocacy (r=0.610), intimacy (r=0.608). The regression test shows that 7 variables have a joint influence with the equation Y: 31.864+1.127*Respect to Others + 1.689*Education + 1.179 Length of Work - 1.919 *class rank + 0.755 Intimacy – 1.975*career level + 1.054 Advocacy. Respect to others partially has a positive effect on nurses' performance in nursing care (t=2.433, p=0.016), while the other variables are confounding variables (p>0.05, t